2008
DOI: 10.1080/09540120701534715
|View full text |Cite
|
Sign up to set email alerts
|

Maternal versus paternal orphans and HIV/STI risk among adolescent girls in Zimbabwe

Abstract: The AIDS epidemic has contributed to a drastic increase in the number of orphans in Zimbabwe. Orphans (whether orphaned by AIDS or other causes) have been shown to have economic and educational disadvantages as well as poor reproductive health outcomes. We recruited a convenience sample of 200 girls in a peri-urban area of Zimbabwe to examine the impact of orphan status (compared to non-orphans) on household composition, education, risk behaviour, pregnancy and prevalent HIV and HSV-2 infection. In our populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 6 publications
3
60
2
Order By: Relevance
“…Paternal orphans were more likely to have ever been homeless and to be out of school (69). Birdthistle et al (70) have also reported higher HIV infection prevalence among orphan girls and women aged 15 to 19 years (17%), as opposed to non-orphan girls (14%).…”
Section: Orphanhood and Hivmentioning
confidence: 81%
“…Paternal orphans were more likely to have ever been homeless and to be out of school (69). Birdthistle et al (70) have also reported higher HIV infection prevalence among orphan girls and women aged 15 to 19 years (17%), as opposed to non-orphan girls (14%).…”
Section: Orphanhood and Hivmentioning
confidence: 81%
“…Orphan status was defined as maternal orphan (having lost a mother), paternal orphan (having lost a father) or double orphan (having lost both parents). Maternal orphan-hood was considered a sign of greater social vulnerability based on previous research [42],[48]. To measure levels of social support received , we adapted a measure developed in Zimbabwe that is used in orphan programming.…”
Section: Methodsmentioning
confidence: 99%
“…began with formative work in 2000,which showed that poverty and gender inequalities increased adolescent women's HIV risk [41], and that that maternal orphans were most vulnerable [42]. Results of a formative phase evaluation of a micro-credit intervention ((4), also described above) led to a radical re-design of the model, based not only on the pilot data, but also on the concepts of agency and gendered poverty as described in Naila Kabeer's Theory of Women's Empowerment [43],[44].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies now confirm that orphaned adolescents are at a significantly higher risk for HIV than their non-orphaned counterparts 40–43. Female adolescent orphans, in particular, have been shown to be at a much higher risk for several different SRH outcomes, including sexually transmitted infections,40 44 pregnancy,41 45 early sexual debut42 43 46 and transactional and forced sex 42 43. It has also been observed that the prevalence of orphaned children in LMIC, especially Sub-Saharan Africa, is much higher in urban areas compared with rural areas, most likely because of the higher HIV prevalence in urban areas 47…”
Section: Introductionmentioning
confidence: 99%